2021
DOI: 10.1186/s12877-021-02688-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in impact of sarcopenia on falls in community-dwelling Korean older adults

Abstract: Background Falls are one of the most serious health problems among older adults. Sarcopenia is characterized by a decrease in muscle mass, strength, and physical function. Due to potentially age-related conditions, both falls and sarcopenia have common risk factors. However, the association between sarcopenia and falls is controversial. Moreover, the sex differences in the impact of sarcopenia on falls is not yet clear. This study aimed to investigate the sex differences in the impact of sarcop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
(32 reference statements)
2
11
0
1
Order By: Relevance
“…Sarcopenia is an important contributor to falls risk, and hence fractures [ 2 ]. We have previously demonstrated relationships between muscle size and grip strength, and bone size and strength, supporting a role for the muscle-bone unit [ 3 ], with stronger relationships in females as it has been observed elsewhere [ 4 , 5 ]. In 2019, the revised European Working Group on Sarcopenia in Older People 2 guidelines were published emphasising muscle strength, relative to muscle mass and function [ 6 ].…”
Section: Introductionsupporting
confidence: 81%
“…Sarcopenia is an important contributor to falls risk, and hence fractures [ 2 ]. We have previously demonstrated relationships between muscle size and grip strength, and bone size and strength, supporting a role for the muscle-bone unit [ 3 ], with stronger relationships in females as it has been observed elsewhere [ 4 , 5 ]. In 2019, the revised European Working Group on Sarcopenia in Older People 2 guidelines were published emphasising muscle strength, relative to muscle mass and function [ 6 ].…”
Section: Introductionsupporting
confidence: 81%
“…The result is consistent with previous research emphasizing sex differences in sarcopenia, and showing that women were more frequently influenced by sarcopenia than men. [26][27][28] We noted that the majority of PSA group members had shorter sleep duration and lower bodyweight. The present results are in line with that of a prospective study.…”
Section: Discussionmentioning
confidence: 75%
“…Studies performed in the general Asian older adult populations with a large sample size revealed a consistent prevalence of sarcopenia ranging from 6% to 12% using the AWGS‐2014 criteria [ 13 , 23 ], while more recent studies using AWGS‐2019 criteria demonstrated the prevalence of sarcopenia ranging from 11% to 18% [ 24 , 25 ]. Our findings supported previous evidence showing a higher prevalence of sarcopenia among PLWH compared with matched HIV‐uninfected populations [ 6 , 8 , 21 , 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%